Parenting Styles, Depressive Symptoms, and Problematic Online Game Use in Adolescents: A Developmental Cascades Model - Gan, Xiong; Li, Hao; Li, Mengmeng; Yu, Chengfu; Jin, Xin; Zhu, Congshu; Liu, Yifan (Frontiers in Public Health, 2021)
Abundant empirical research has demonstrated the relationship between parenting style and adolescent problematic online game use (POGU), but the direction and underlying mechanism of this association remain unclear. Using a 1-year longitudinal design across three time points, the present study explored interrelations among parenting styles, depressive symptoms, and POGU from the theoretical perspective of the developmental cascade model and examined whether depressive symptoms mediate the relationship between parenting style and POGU. A sample of 1,041 children was recruited from two junior middle schools in China, of which 46.3% were boys. Results confirmed the cascade effects and showed that the reciprocal effect of parenting style, depressive symptoms, and POGU was significant, and parental control and POGU can predict each other via depressive symptoms. Knowledge regarding the direct and underlying mechanisms between parenting style, depressive symptoms, and POGU provides reference suggestions for the prevention and intervention of adolescent depressive symptoms and problematic online game use.